2021
DOI: 10.1002/pmic.202000138
|View full text |Cite
|
Sign up to set email alerts
|

In‐depth proteome of perilymph in guinea pig model

Abstract: The vast majority of sensorineural hearing loss is caused by impairment of the inner ear cells. Proteomic analysis of perilymph may therefore improve our understanding of inner ear diseases and hearing loss. However, the investigation of the human perilymph proteome was limited due to technical difficulties in perilymph sampling. The guinea pig (Cavia porcellus) is frequently used as an experimental model in preclinical hearing research. In this study, we analyzed samples of perilymph collected from 12 guinea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Human perilymph sample preparation in the IT steroid‐treated group ( n = 19) and non‐treated group ( n = 9) was performed as described previously, with some modifications [5]. Samples were collected from nine individuals each from the IT steroid‐treated group and the non‐treated group, and the perilymph sample was extracted from either side of the inner ear.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Human perilymph sample preparation in the IT steroid‐treated group ( n = 19) and non‐treated group ( n = 9) was performed as described previously, with some modifications [5]. Samples were collected from nine individuals each from the IT steroid‐treated group and the non‐treated group, and the perilymph sample was extracted from either side of the inner ear.…”
Section: Methodsmentioning
confidence: 99%
“…LC‐MS/MS analysis was performed using an Ultimate 3000 RSLC system (Dionex, USA) connected to a Q‐Exactive Plus mass spectrometer (Thermo Scientific, Bremen, Germany) with nano‐electrospray [5]. Briefly, the peptide samples were separated using a two‐column system with a trap column (300 μm I.D.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Target-oriented local delivery methods such as intratympanic (IT) injection of dexamethasone (D) have been introduced as alternative methods. Due to direct absorption through the round window membrane (RWM), IT injection can achieve a higher concentration of steroid in the perilymph compared with systemic administration [ 7 , 8 , 9 , 10 , 11 ]. A systematic review showed that IT steroids can be a valuable solution for patients with acute SNHL who either cannot tolerate systemic steroid therapy or do not respond to treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%